Prevalence of Smartphone Addiction during COVID-19 Pandemic Lockdown and Its Impact on Online Learning in Kathmandu - Maharjan, Rocky (Mangal Research Journal, 2021)
The COVID-19 pandemic lockdown has encouraged students to use their smartphones in online classes and stay connected increasingly. Youths are using smartphone in COVID-19 pandemic more often than before. The present study aims to find prevalence of smartphone addiction during COVID-19 pandemic and its impact on BBA students' online learning in Kathmandu district. The questionnaire with Smartphone Addiction Scale- Short Version (SAS-SV) and smartphone using pattern was circulated through emails to collect data from four hundred students of 8 different BBA colleges in Kathmandu district using a convenience sampling method. After omitting incomplete data and exclusion criteria, overall 280 responses including 123 males and 157 females were recorded at a response rate of 70%. The result found the mean score of smartphone addiction of 34.67±9.29. Nearly half participants 48.93% (n=137) were found smartphone addicted. The study further revealed that gender was not associated with smartphone addiction but the time spent on smartphone in a day and age group was significantly associated with smartphone addiction. This study found that smartphone use is a contributing element to the success of online learning during COVID-19 pandemic. These results suggest the need to develop educational programme to educate the students to use smartphone effectively.